Cardiovascular events associated with the long-term use of NSAIDs: a review of randomized controlled trials and observational studies. (May 2014) - Salvo, Francesco; Antoniazzi, Stefania; Duong, Mai; Molimard, Mathieu; Bazin, Fabienne; Fourrier-Réglat, Annie; Pariente, Antoine; Moore, Nicholas
<x xml:space="preserve">Abstract</x> Introduction: An increased risk of cardiovascular thrombotic events in users of NSAIDs was first demonstrated for rofecoxib. This risk seems to be related to the COX-2 inhibitory potency and has been found with most NSAIDs except naproxen. Two main hypotheses have been advanced: an imbalance between COX-1-dependent platelet production of thromboxane and partly COX-2-dependent endothelial production of prostacyclin, and a COX-2-dependent increase in blood pressure. Areas covered: Clinical trials and observational studies providing information about cardiovascular risk associated with long-term use of NSAIDs were retrieved; 14 clinical trials and 16 observational studies mentioned a follow-up of at least 6 months. Expert opinion: Results are ambiguous: long-term exposure seemed associated with an increased risk of myocardial infarction or stroke with high-dose rofecoxib, and perhaps diclofenac, but less with other NSAIDs. In other studies, little or no increase in risk was associated with exposures shorter than 30 days. Since most NSAIDs are rarely used long term, there is little information on risks associated with long-term use. The relative risks or odds ratios associated with most drugs are mostly well below 2.